Chronic airflow obstruction after successful treatment of multidrug-resistant tuberculosis. Issue 3 (12th July 2017) - Byrne, Anthony L.; Marais, Ben J.; Mitnick, Carole D.; Garden, Frances L.; Lecca, Leonid; Contreras, Carmen; Yauri, Yaninna; Garcia, Fanny; Marks, Guy B.
Cross-sectional studies reveal an association between tuberculosis (TB) and chronic airflow obstruction, but cannot adequately address confounding. We hypothesised that treated pulmonary TB is an independent risk factor for chronic airflow obstruction. The Pulmones Post TB cohort study enrolled participants from Lima, Peru, aged 10–70 years with a history of drug-susceptible (DS)- or multidrug-resistant (MDR)-TB who had completed treatment and were clinically cured. Unexposed participants without TB were randomly selected from the same districts. We assessed respiratory symptoms, relevant environmental exposures, and spirometric lung function pre- and post-bronchodilator. In total, 144 participants with DS-TB, 33 with MDR-TB and 161 unexposed participants were fully evaluated. Compared with unexposed participants, MDR-TB patients had lower lung volumes (adjusted mean difference in forced vital capacity −370 mL, 95% CI −644– −97) and post-bronchodilator airflow obstruction (adjusted OR 4.89, 95% CI 1.27–18.78). Participants who had recovered from DS-TB did not have lower lung volumes than unexposed participants, but were more likely to have a reduced forced expiratory volume in 1 s/forced vital capacity ratio <0.70 (adjusted OR 2.47, 95% CI 1.01–6.03). Individuals successfully treated for TB may experience long-lasting sequelae. Interventions facilitating earlier TB treatment and management of chronic respiratory disease should be explored. Treated MDR-TB results in loss of lung volume; MDR-TB and susceptible TB can result in chronic airflow obstruction http://ow.ly/yM9H30bRDha